Basic Ionic Liquid HEAA Catalysed One-Pot Synthesis of Novel 2-Amino-3-Phenylsulfonyl-4H-Pyrans Derivatives. (December 2013) - Ding, Maohua; Zhang, Lei; Guo, Hongyun; Zhong, Mingqiang
An efficient preparation of novel 2-amino-3-phenylsulfonyl-4H-pyrans derivatives is reported by the condensation of aromatic aldehydes, dimedone and phenylsulfonylacetonitrile in the presence of 2-hydroxyethyl ammonium acetate [H3 N + CH2 CH2 OH] [CH3 COO - ] (HEAA) as suitable and efficient catalyst. This method offers some distinct advantages such as short reaction time, high yields, and simple procedure.